2016
DOI: 10.3892/ol.2016.4186
|View full text |Cite
|
Sign up to set email alerts
|

Thickness of preperitoneal fat as a predictor of malignancy in overweight and obese women with endometrial polyps

Abstract: Abstract. The aim of the present study was to determine the association between the thickness of preperitoneal fat (PFT), utilized as an indicator of visceral fat deposition, and the risk of premalignant and malignant changes of endometrial polyps (EPs) in overweight and obese women. Overweight and obese women who had undergone diagnostic outpatient hysteroscopy and subsequent endometrial polypectomy between January 2010 and May 2013 were analyzed. Each patient underwent a transabdominal ultrasound for the pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
4
7
1
Order By: Relevance
“…Preperitoneal fat has been related to increased risk of malignancies in women. 26 As previously published, 27 an association between fatty liver disease and preperitoneal fat thickness was found. Therefore, for those with less ultrasound use experience, assessing…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Preperitoneal fat has been related to increased risk of malignancies in women. 26 As previously published, 27 an association between fatty liver disease and preperitoneal fat thickness was found. Therefore, for those with less ultrasound use experience, assessing…”
Section: Discussionsupporting
confidence: 65%
“…Fat is much thicker close to the xiphoid appendix and thinner inside the pelvic area, where most of the gynaecological measures are made. 26 In this study, another a significant correlation between fatty liver and perirenal fat depot thickness has also been described.…”
Section: Discussionsupporting
confidence: 58%
“…The PFT was defined as the thickness of the fat tissue between the liver surface and the linea alba. As previously described, 22,23 the PFT was measured with the patient in the supine position, through a longitudinal scanning with a 1 to 5 MHz convex probe (4C-A H46701AA; GE Healthcare Bio-Sciences) held perpendicular to the skin at the epigastrium. All images were captured immediately following a breath to avoid the influence of abdominal wall tension or respiratory status.…”
Section: Ultrasound Assessmentsmentioning
confidence: 99%
“…The rate of unexpected cancer in AEH may be affected by some EC predictors, and the endometrial sampling method (ESM) used preoperatively [7][8][9][10][11][12]. Previous studies have shown that some cancer predictors in women with AEH are associated with concurrent EC [13,14].…”
Section: Introductionmentioning
confidence: 99%